PENGARUH EKSTRAK DAUN KELOR (Moringa oleifera Lam) TERHADAP KADAR KREATININ, UREUM DAN HISTOLOGI GINJAL TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI ETILEN GLIKOL - Abdul Karim (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2026)
Cases of kidney failure in children have become a public topic in Indonesia in recent years. Acute kidney failure in children is suspected to be related to syrup medication as a causative factor. The syrup suspected of causing kidney failure in children is suspected to be contaminated with ethylene glycol. Ethylene glycol is a compound that can generate free radicals, thus damaging the kidneys. This study aims to examine the effect of Moringa oleifera leaf extract (Moringa oleifera Lam.) on the morphology, histology, and physiology of the kidneys of white rats induced by ethylene glycol. This study used RAL with 20 rats divided into 5 groups, namely the normal control group (feed and drink), the sick control group (0.75% ethylene glycol ad libitum), the Mo 150 treatment group (0.75% ethylene glycol ad libitum and 150 mg/kg BW moringa leaf extract), the Mo 300 treatment group (0.75% ethylene glycol ad libitum and 300 mg/kg BW moringa leaf extract), the Mo 450 treatment group (0.75% ethylene glycol ad libitum and 450 mg/kg BW moringa leaf extract). The stages in this study include phytochemical screening, antioxidant activity testing, total flavonoids, morphological observations, relative organ weight index, scoring of kidney histology damage, examination of kidney urea creatinine levels of white rats. Data analysis used One Way ANOVA and Duncan test. The research results obtained from Moringa leaves did not affect kidney morphology, but had an effect on reducing the relative weight of the organ, scoring of kidney histology damage, creatinine levels, and urea, namely at a dose of 450 mg/kg BW which was effective in reducing the impact of damage due to ethylene glycol administration